Phenotype databases for genetic screens in human cells - Rauscher, Benedikt; Valentini, Erica; Hardeland, Ulrike; Boutros, Michael (Journal of biotechnology, 2017)
Genetic screens are powerful tools to identify components that make up biological systems. Perturbations introduced by methods such as RNA interference (RNAi) or CRISPR/Cas9-mediated genome editing lead to biological phenotypes that can be examined to understand the molecular function of genes in the cell. Over the years, many of such experiments have been conducted providing a wealth of knowledge about genotype-to-phenotype relationships. These data are a rich source of information and it is in a common interest to make them available in a simplified and integrated format. Thus, an important challenge is that genetic screening data can be stored in databases in standardized ways, allowing users to gain new biological insights through data mining and integrated analyses. Here, we provide an overview of available phenotype databases for human cells. We review in detail two databases for high-throughput screens, GenomeRNAi and GenomeCRISPR, and describe how these resources are integrated into the German Network for Bioinformatics Infrastructure de.NBI as part of the European infrastructure for life-science information ELIXIR.